Unveiling the therapeutic potential of traditional Chinese medicine Rhizome Coptidis: A comprehensive review - Kuldeep Singh; Jeetendra Kumar Gupta; Divya Jain; Alka N Chaudhary; Shivendra Kumar; Mukesh Chandra Sharma; Bhupendra Singh (Pharmacological Research - Modern Chinese Medicine)
Introduction: R. coptidis, also known as Huang Lian in Chinese, has been a cornerstone of TCM for centuries. Its bitter and cold properties make it a versatile herb for treating various ailments. While traditionally used to clear heat, eliminate dampness, and alleviate toxicity, recent scientific investigations have revealed various pharmacological activities beyond its traditional applications. Methods: A Comprehensive review of scientific databases, including PubMed, Web of Science, and Chinese medical literature databases, was conducted to gather comprehensive insights. The keywords used included ''R. coptidis,'' ''Huang Lian,'' ''pharmacological properties,'' ''therapeutic applications,'' and ''Traditional Chinese Medicine.'' Studies from both in vitro and in vivo experiments were considered, ensuring a well-rounded evaluation of the herb's effects. Results: The pharmacological properties of R. coptidis are attributed to its main bioactive component, berberine. In various studies, Berberine has demonstrated antimicrobial, anti-inflammatory, antioxidant, antidiabetic, and anticancer activities. Furthermore, its effects on metabolic disorders, cardiovascular health, and neuroprotection have sparked interest in its potential therapeutic applications. Discussion: The diverse pharmacological effects of R. coptidis stem from its interactions with multiple molecular targets. Berberine's ability to modulate signaling pathways and gene expression has garnered attention as a promising candidate for drug development. However, challenges such as bioavailability and potential herb-drug interactions warrant further investigation. Conclusion: In conclusion, R. coptidis holds immense promise as a therapeutic agent beyond its traditional uses in TCM. The rich pharmacological profile of berberine suggests its potential in addressing various health conditions. Nonetheless, rigorous clinical trials and translational research are necessary to bridge the gap between traditional wisdom and modern medical applications. As research continues, R. coptidis may emerge as a fundamental herb in TCM and contemporary medicine.